Defect-mediated ripening of core-shell nanostructures - Zhang, Qiubo (2022)
Understanding nanostructure ripening mechanisms is desirable for gaining insight on the growth and potential applications of nanoscale materials. However, the atomic pathways of nanostructure ripening in solution have rarely been observed directly. Here, we report defect-mediated ripening of Cd-CdCl2 core-shell nanoparticles (CSN) revealed by in-situ atomic resolution imaging with liquid cell transmission electron microscopy. We find that ripening is initiated by dissolution of the nanoparticle with an incomplete CdCl2 shell, and that the areas of the Cd core that are exposed to the solution are etched first. The growth of the other nanoparticles is achieved by generating crack defects in the shell, followed by ion diffusion through the cracks. Subsequent healing of crack defects leads to a highly crystalline CSN. The formation and annihilation of crack defects in the CdCl2 shell, accompanied by disordering and crystallization of the shell structure, mediate the ripening of Cd-CdCl2 CSN in the solution.